2022
DOI: 10.1681/asn.2021111472
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Repeated Rituximab to Maintain Remission in Idiopathic Childhood Nephrotic Syndrome: An International Study

Abstract: Background: Long-term outcomes following multiple rituximab courses among children with frequently-relapsing, steroid-dependent nephrotic syndrome (FRSDNS) are unknown. Methods: A retrospective cohort study at 16 pediatric nephrology centers from 10 countries in Asia, Europe, and North America included children with FRSDNS who received ≥2 rituximab courses. Primary outcomes were relapse-free survival and adverse events. Results: 346 children (age 9.8 years, IQR 6.6-13.5; 73% boys) received 1149 rituximab cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
2
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 50 publications
7
39
2
3
Order By: Relevance
“…Evidence for the most correct approach is lacking [ 164 ]. Based on a recent retrospective survey, 30 of 346 included children tolerated up to 7 courses of RTX infusions (mainly dosed with 375 mg/m 2 /course) with an acceptable side effect profile (most common hypogammaglobulinema, followed by infections and neutropenia) and good efficacy [ 182 ].…”
Section: Relapsing Ssns: Second Line Treatmentmentioning
confidence: 99%
“…Evidence for the most correct approach is lacking [ 164 ]. Based on a recent retrospective survey, 30 of 346 included children tolerated up to 7 courses of RTX infusions (mainly dosed with 375 mg/m 2 /course) with an acceptable side effect profile (most common hypogammaglobulinema, followed by infections and neutropenia) and good efficacy [ 182 ].…”
Section: Relapsing Ssns: Second Line Treatmentmentioning
confidence: 99%
“…Rituximab has emerged as an important therapeutic option in several pediatric immunemediated glomerular diseases, such as idiopathic nephrotic syndrome and ANCA-associated vasculitis glomerulonephritis. 2,22,23 Our data showed that rituximab exposure up to 1 year prior to vaccination resulted in poor immunogenicity. Furthermore, patients with glomerular disease are at risk of relapse and often require multiple courses of rituximab to maintain disease remission.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, patients with glomerular disease are at risk of relapse and often require multiple courses of rituximab to maintain disease remission. 22 Therefore, the timing of vaccination and rituximab should be individualized, balancing the risk of infection and disease relapse. Fortunately, our current findings did not suggest an overtly increased risk of graft rejection and disease relapse following vaccination, indicating the safety of COVID-19 vaccination in children and adolescents with kidney diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chief concerns associated with therapy have been the risks of infusion reactions (4 studies, 252 children; RR 5.8, 95% CI 1.3-25.3) [25], severe infections [32], vaccine hyporesponsiveness [33], and reactivation of viral infections, such as hepatitis B and JC virus [34]. Recent studies suggest that therapy may lead to variable hypogammaglobulinemia in 35-58% of children, particularly in patients < 8-10 years old, those with preexisting hypogammaglobulinemia, and those receiving multiple rituximab doses or additional immunosuppression [35].…”
Section: Steroid-sparing Medicationsmentioning
confidence: 99%